2021
DOI: 10.2196/27882
|View full text |Cite
|
Sign up to set email alerts
|

The Dutch COVID-19 Contact Tracing App (the CoronaMelder): Usability Study

Abstract: Background Adoption and evaluation of contact tracing tools based on information and communications technology may expand the reach and efficacy of traditional contact tracing methods in fighting COVID-19. The Dutch Ministry of Health, Welfare and Sports initiated and developed CoronaMelder, a COVID-19 contact tracing app. This app is based on a Google/Apple Exposure Notification approach and aims to combat the spread of the coronavirus among individuals by notifying those who are at increased risk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 18 publications
(12 reference statements)
0
28
0
Order By: Relevance
“…It would, therefore, be important for app developers to gain in-depth insight into the issues that former users have experienced. Moreover, additional usability research could be conducted, as previous research among potential users found issues related to the understandability of CTAs, doubts concerning their usefulness and privacy, and which follow-up actions were expected after a risk exposure notification [ 47 ]. Moreover, previous research analyzing media content concerning the implementation of CTAs has identified thresholds and challenges experienced by users and showed the need to intensify communication about the benefits of using the apps [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would, therefore, be important for app developers to gain in-depth insight into the issues that former users have experienced. Moreover, additional usability research could be conducted, as previous research among potential users found issues related to the understandability of CTAs, doubts concerning their usefulness and privacy, and which follow-up actions were expected after a risk exposure notification [ 47 ]. Moreover, previous research analyzing media content concerning the implementation of CTAs has identified thresholds and challenges experienced by users and showed the need to intensify communication about the benefits of using the apps [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since this study, the mobile apps, announced by the Dutch Government in April 2020, have been developed and implemented. In a recent study by Bente et al [ 15 ], the contact tracing app (the CoronaMelder) was tested for usability, and was found easy to use. A comparable study was executed in Germany by Blom et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our survey was distributed before the development of the CoronaMelder app in the Netherlands. The study by Bente et al [ 15 ] indicated that during this period there were many misconceptions concerning contact tracing among the Dutch population. It is likely that these short descriptions of the general aim of the 2 mobile apps were insufficient to take those misconceptions away.…”
Section: Discussionmentioning
confidence: 99%
“…The use of technology in the form of digital applications, platforms and artificial intelligence systems has been proposed as a possible strategy to increase the coverage and effectiveness of contact tracing [25][26][27][28][29][30]. However, issues around privacy, administrative organisation, legal, ethical and cultural considerations have emerged as hurdles to the wider use of technological platforms that could contribute to the effectiveness of contact tracing services [31][32][33][34][35][36]. In addition, the real impact and effectiveness of various technological approaches has not been vigorously evaluated and more research is needed [37,38].…”
Section: Discussionmentioning
confidence: 99%